1.y'' + 3y = −48x2e3x.
Solution:
y'' + 3y=0
"\\lambda"2+3 =0
"\\lambda" 1=-i31/2, "\\lambda" 2=i31/2.
y0(x)=c1cos(31/2 x)+c2sin(31/2x),
yp(x)=(Ax2+Bx+C)e3x
yp'(x)=(3Ax2+(3B+2A)x+3C+B)e3x
yp''(x)=(9Ax2+(9B+12A)x+2A+6B+9C)e3x
x2e3x:3A+9A=-48,
xe3x:3B+9B+12A=0,
e3x:3C+2A+6B+9C=0.
=>A=-4,B=4,C=-4/3.
yp(x)=(-4x2+4x-4/3)e3x,
y(x)=y0(x)+yp(x)
Answer:
y(x)=c1cos(31/2 x)+c2sin(31/2x)+(-4x2+4x-4/3)e3x
2.y(4) + 2y'' + y = cos x − 3x sin x
Solution:
y(4) + 2y'' + y =0
"\\lambda" 4+2"\\lambda" 2+1=0
("\\lambda" 2+1)2=0
"\\lambda" 1=-i, k=2,
"\\lambda"2 =i, k=2
yp(x)=(Ax3+Bx2)cos(x)+(Cx3+Dx2)sin(x)
yp'(x)=...,yp''(x)=...yp'''(x)=...,y(4)(x)=...
yp(4) + 2yp'' + yp=cos(x)(-24Ax-8B+24C)+sin(x)(-24A-24Cx-8D)
-24A=0
-8B+24C=1
-24C=3
-24A-8D=0
=>A=0,B=1/4, C=1/8, D=0
Answer:
yp(x)=x2/4cos(x)+x3/8sin(x)
Comments
Leave a comment